Knowledge, Attitude and Behavior of Methodist 2 Palembang High School Student towards Clean and Healthy Lifestyle (PHBS) - Christine, Theodora; Rivami, Dwi Savitri (Medicinus, 2021)
Background: Clean and Healthy Lifestyle or namely PHBS (Perilaku Hidup Bersih dan Sehat) in Indonesia is a program from the Indonesian Ministry of Health that has been implemented since 1996. PHBS in school settings is very important to be realized in order to create a clean and healthy school environment so that the learning and teaching process can run effectively.Aims: This study aims to describe the knowledge, attitudes, and behavior of Methodist 2 High School students towards PHBS. In addition, this study also aims to see the relationship between PHBS knowledge and attitudes towards PHBS behavior in Methodist 2 Palembang High school studentsMethods: This study uses a cross-sectional study involving 216 students obtained by calculating unpaired categorical analytic samples. Samples were taken using the purposive sampling technique. Data was collected using a questionnaire distributed online via a google form. The data obtained were processed using Chi-Square through the SPSS 25.Results: There were 216 respondents who met the inclusion and exclusion criteria of this study. The sample consisting of female (n=124 (57.4%)) and male (n=92 (42.6%)) and distributed evenly from 1st grade to 3rd grade (1st grade n=65 (30.1%), 2nd grade n=75 (34.7%), 3rd grade n=76 (35.2%)). Using average value as cut-off point (12.7), most of the students of Methodist 2 Palembang high school had sufficient knowledge of PHBS (n=132 (61%), and the rest of it had insufficient knowledge of PHBS (n=84 (38,9%)). With a median value (57.6) as the cut-off point, it showed that most of the students had a sufficient PHBS attitude (n=118 (54.6%)) and the rest of it had an insufficient attitude of PHBS (n=98 (45,5%)). With an average value (13.2) as a cut-off point, most of the students had insufficient PHBS behavior (n=102 (52.8%)) and the rest of it had sufficient behavior of PHBS (n=102 (42,7%)). The results of the analysis found that there was no significant relationship between knowledge and PHBS behavior among Methodist 2 Palembang high school students (p-value = 0.744) and there was a significant relationship between PHBS attitudes towards PHBS behavior among Methodist 2 Palembang high school students (p-value = <0.001)